Comparison of harvesting methods and clinical application of apheresis platelet concentrates with additive solution - O. V. Karpova; I. V. Obraztsov; P. E. Trakhtman; A. A. Ignatova; M. A. Panteleev; S. A. Rumyantsev (Онкогематология)
Platelet concentrates (PC) are used worldwide in the fields of oncology, oncohaematology and bone marrow transplantation. One of the main tasks of clinical transfusiology is the development and improvement of technologies aimed to increase quality and safety of PC. In particular, such technologies are represented by using of platelet additive solutions (PAS). The main advantages of this approach are: a reduction of immune and non-immune transfusion reactions risk, an improvement of pathogen inactivation quality and enhancing a clinical effect of PC transfusions after storage. Numerous different PAS and methodologies of their application are suggested to date. In this review we have described and classified recent data on different PAS and the benefits of their clinical application.